The Contribution of al-'Ilm Sharaf To the Development of Understanding Classical Arabic Grammar at Islamic Educational Institutions - Nurbaiti, Nurbaiti (Al-Fikrah, 2024)
This study examines the contribution of al-'Ilm Sharaf to the development of understanding classical Arabic grammar in Islamic educational institutions. Al-'Ilm Sharaf is a key branch of Arabic grammar that focuses on word formation and meaning through the manipulation of root letters. Although this subject has been integrated into the curriculum, there is still a gap between theoretical knowledge and its practical application. This research employs a library research method to gather data from various relevant written sources. The findings show that students often struggle to apply the theoretical aspects of Arabic morphology when analyzing classical texts, and al-'Ilm Sharaf instruction requires a more interactive and practice-based approach. Therefore, this study offers valuable insights into how teaching methods and materials can be improved to enhance students' comprehension of classical Arabic grammar.